2005
DOI: 10.1016/j.febslet.2005.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Topors acts as a SUMO‐1 E3 ligase for p53 in vitro and in vivo

Abstract: Human Topors, which was originally identified as cellular binding partner of DNA topoisomerase I and of p53, has recently been shown to function as an ubiquitin E3 ligase for p53 in a manner dependent on its N 0 -terminally located RING finger. Here, we demonstrate that Topors also enhances the conjugation of the small ubiquitin-like modifier 1 (SUMO-1) to p53 in vivo and in a reconstituted in vitro system. The Topors SUMO-1 E3 ligase activity does not depend upon its RING finger motif. In HeLa cells, Topors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 26 publications
5
123
0
Order By: Relevance
“…Precedent for such a dual-activity protein is provided by the conserved RING-finger protein, Topors. Topors binds DNA topoisomerase I [50] and p53 [51,52] and it displays both Ub E3 ligase [53,54] and SUMO ligase activity [55]. Topors Ub ligase activity is dependent on its RING-finger domain, while its SUMO ligase activity is not [55].…”
Section: Discussionmentioning
confidence: 99%
“…Precedent for such a dual-activity protein is provided by the conserved RING-finger protein, Topors. Topors binds DNA topoisomerase I [50] and p53 [51,52] and it displays both Ub E3 ligase [53,54] and SUMO ligase activity [55]. Topors Ub ligase activity is dependent on its RING-finger domain, while its SUMO ligase activity is not [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that wild type p53 protein is modified by SUMO. Topors SUMO-1 E3 ligase enhances the conjugation of SUMO-1 to p53 at lysine 386 in vivo (60). SUMO ligases PIAS1 and PIASx␤ together with Ubc9-conjugating enzyme modify p53 at lysine 386 and repress the transcriptional activity of p53 (61).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro sumoylation reactions were also performed with p53 as a substrate (40,41). Limiting amounts of Ubc9 were used and SUMO3 conjugation to p53 was hardly detectable at early timepoints.…”
Section: Sf2/asf Interacts With Ubc9 and Stimulates Sumoylation Of Spmentioning
confidence: 99%